Extensive variation in chromatin states across humans - Kasowski, Maya; Kyriazopoulou-Panagiotopoulou, Sofia; Grubert, Fabian; Zaugg, Judith B.; Kundaje, Anshul; Liu, Yuling; Boyle, Alan P.; Zhang, Qiangfeng Cliff; Zakharia, Fouad; Spacek, Damek V.; Li, Jingjing; Xie, Dan; et al. (Science, 2013)
DNA Differences - The extent to which genetic variation affects an individual's phenotype has been difficult to predict because the majority of variation lies outside the coding regions of genes. Now, three studies examine the extent to which genetic variation affects the chromatin of individuals with diverse ancestry and genetic variation (see the Perspective by Furey and Sethupathy). Kasowski et al. (p. 750, published online 17 October) examined how genetic variation affects differences in chromatin states and their correlation to histone modifications, as well as more general DNA binding factors. Kilpinen et al. (p. 744, published online 17 October) document how genetic variation is linked to allelic specificity in transcription factor binding, histone modifications, and transcription. McVicker et al. (p. 747, published online 17 October) identified how quantitative trait loci affect histone modifications in Yoruban individuals and established which specific transcription factors affect such modifications. - The majority of disease-associated variants lie outside protein-coding regions, suggesting a link between variation in regulatory regions and disease predisposition. We studied differences in chromatin states using five histone modifications, cohesin, and CTCF in lymphoblastoid lines from 19 individuals of diverse ancestry. We found extensive signal variation in regulatory regions, which often switch between active and repressed states across individuals. Enhancer activity is particularly diverse among individuals, whereas gene expression remains relatively stable. Chromatin variability shows genetic inheritance in trios, correlates with genetic variation and population divergence, and is associated with disruptions of transcription factor binding motifs. Overall, our results provide insights into chromatin variation among humans. - Variability among humans with different ancestry affects chromatin states and gene expression. [Also see Perspective by Furey and Sethupathy] - Variability among humans with different ancestry affects chromatin states and gene expression. [Also see Perspective by Furey and Sethupathy]